(untitled) (Fiep Bulletin - online, 2013)
The purpose of this study was to examine the position in the school environment for children to a private school education network in the city of Manaus. The sample of 60 children, between 8 and 14 years old, from 3rd to 8th grade. The subjects were filmed in writing simulation, with the feet supported on the ground or in this direction. For data processing system using the Peak Motus. The knee and ankle angles of the four groups showed average values for groups of 3 and 8 series of more than 4 series and 5 series, due to the furniture it is not used in accordance with the children anthropometry, the popliteal region, which is supported on the front seat, has increased the compression result of the absence of the foot contact with the ground and can cause problems in blood circulation of this region. Comparing the samples that exist in the furniture with regulatory standards adopted by the School, it was found that the furniture used for the classes are not examined in accordance with the children anthropometry. In the analysis of the angles there was no difference between the groups, but the groups take in school furniture favors for the generation of bodily pain. These results indicate that the institutions of elementary school should hold a special attention to the securities they use in the classroom and do postural guidelines for that damage to structures osteomioarticulares can be minimized in the school in question.